Argentine Navy Icebreaker Ship “Almirante Irizar” Sludge Microbial Composition Analysis for Biohydrogen Production - García, Rodrigo Enrique; Pin Viso, Natalia Daniela; Gerosa, Fernando Ariel; Nishinakamasu, Verónica Cecilia; Puebla, Andrea Fabiana; Farber, Marisa Diana; Lavorante, Maria Jose (BioEnergy Research)
Sludge from the wastewater treatment plant of the Argentinean Navy icebreaker ship “Almirante Irizar” was used as inoculum for biohydrogen production. The bacterial community was monitored throughout the fermentation, by sequencing 16S rRNA amplicons, to establish the microbial dynamics of the bioreactor over time. The established operating procedure assured a hydrogen content, along the process, in the range of 59.2–70.0%. The predominant species found were Clostridium sensu stricto and Sporolactobacillus sp. Clostridium showed higher values in the beginning of the fermentation with more than 90% of relative abundance. Conversely, Sporolactobacillus reached values close to 20% at its end. Additional topics discussed are the role of lactic acid bacteria in fermentative biohydrogen production systems and a series of in-process parameters that would allow control of this population. The results obtained allow supporting the use of this type of sludge as a source of hydrogen-producing bacteria. Fil: García, Rodrigo Enrique. Ministerio de Defensa. Instituto de Investigaciones Científicas y Técnicas para la Defensa; Argentina Fil: Pin Viso, Natalia Daniela. Instituto Nacional de Tecnología Agropecuaria. Centro de Investigación En Ciencias Veterinarias y Agronómicas. Instituto de Agrobiotecnología y Biología Molecular. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Instituto de Agrobiotecnología y Biología Molecular; Argentina Fil: Gerosa, Fernando Ariel. Ministerio de Defensa. Instituto de Investigaciones Científicas y Técnicas para la Defensa; Argentina Fil: Nishinakamasu, Verónica Cecilia. Instituto Nacional de Tecnología Agropecuaria. Centro de Investigación En Ciencias Veterinarias y Agronómicas. Instituto de Agrobiotecnología y Biología Molecular. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Instituto de Agrobiotecnología y Biología Molecular; Argentina Fil: ...